2018
DOI: 10.3389/fpsyg.2018.00407
|View full text |Cite
|
Sign up to set email alerts
|

Empathy Modulates the Evaluation Processing of Altruistic Outcomes

Abstract: Empathy plays a central role in social decisions involving psychological conflict, such as whether to help another person at the cost of one’s own interests. Using the event-related potential (ERP) technique, the current study explored the neural mechanisms underlying the empathic effect on the evaluation processing of outcomes in conflict-of-interest situations, in which the gain of others resulted in the performer’s loss. In the high-empathy condition, the beneficiaries were underprivileged students who were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 64 publications
0
16
0
2
Order By: Relevance
“…A growing number of ERP studies have begun to explore how the brain responds to outcomes related to others and found that ERP responses to others' feedback were similar to those elicited by the outcome of participants themselves (Fukushima & Hiraki, 2006Hu, Xu, & Mai, 2017;Liu, Hu, Shi, & Mai, 2018;Yu & Zhou, 2006;Zhu et al, 2018). Yu and Zhou (2006) reported that the FRN was elicited when individuals observed others' performance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A growing number of ERP studies have begun to explore how the brain responds to outcomes related to others and found that ERP responses to others' feedback were similar to those elicited by the outcome of participants themselves (Fukushima & Hiraki, 2006Hu, Xu, & Mai, 2017;Liu, Hu, Shi, & Mai, 2018;Yu & Zhou, 2006;Zhu et al, 2018). Yu and Zhou (2006) reported that the FRN was elicited when individuals observed others' performance.…”
Section: Introductionmentioning
confidence: 99%
“…Although the processing of others' outcomes is similar to that of one's own outcomes, the valence effect of the FRN and P300 amplitude are consistently smaller for others' outcomes than for one's own outcomes. (Fukushima & Hiraki, 2006Koban, Pourtois, Bediou, & Vuilleumier, 2012;Leng & Zhou 2010;Li et al, 2010;Li, Han, Lei, Holroyd, & Li, 2011;Liu, Hu, Shi, & Mai, 2018;Marco-Pallares, Kramer, Strehl, Schroder, & Munte, 2010). Marco-Pallares et al (2010) further explored the temporal processing of outcome evaluation when participants' interests were relevant to the others' performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Montalan et al (2012) adopted Minimal Group Paradigm (participants were randomly assigned to different groups: e.g., underestimator and overestimator group in the dot estimation task) to investigate the empathy preference, and found higher pain empathy to in-group members and lower empathy to out-group members in imagined pain empathy condition. Such brain activity of empathy has been shown to be able to predict the altruism motivation (Mathur et al, 2010; Xin et al, 2018) or costly helping (Hein et al, 2010; Preis et al, 2013). Moreover, as an interesting intergroup emotion, schadenfreude (Dasborough and Harvey, 2017) has also been found in neuroscience (Steinbeis and Singer, 2014; Vollberg and Cikara, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The dFRN data were analyzed in a 2 (Trials type: trials involving monetary payoffs vs. non‐monetary payoffs) × 2 (Participant's decision: cooperation vs. aggression) repeated measures ANOVA. According to previous studies (Liu et al., 2018; Lu et al., 2020), we regarded the absolute value of dFRN as the index measuring the FRN difference. The main effect of the Trials type was significant [ F (1, 29) = 5.46, p = .027, ƞ p 2 = 0.16], suggesting that the dFRN was stronger in the monetary trials ( M = −2.55 μV, SD = 3.42 μV) than in the non‐monetary trials ( M = −1.08 μV, SD = 2.46 μV).…”
Section: Resultsmentioning
confidence: 99%